DELIBERATING TRANSLATION STRATEGIES FOR IDIOMATIC EXPRESSIONS ON THE LITERARY WORK - Akhmad Baihaqi (XXXXXXXX, 2024)
Abstract. It is challenging to analyze the translation of idiomatic expressions since these are common to use in any kind of literary works. In translating those expressions, the translators may encounter several problems since they cannot be translated literally. To solve the problems, an appropriate translation strategy is needed. Therefore, the objective of this current work is to investigate the translation strategy of idiomatic expressions used in the literary work. To achieve such an objective, qualitative content analysis was used for this study. Data of the research were collected from The Maze Runner novel written by James Dashner (published in 2009) and its Indonesian version which was translated by Yunita Chandra (published in 2011). The data collecting technique used for this study was documentation. The result of the study proves that the strategies used by the translator for the novel are (1) similar meaning but with dissimilar form (17%), (2) translation by omission (17%), and (3) translation by paraphrase (66%). The uses of those strategies are required to result in accuracy for translation version of literary work which focuses on the naturalness of nuances of meaning and the context.